Towards a complete project oriented risk management model: A refinement of PRORISK - Boriwat Suebkuna (2018)
PRORSK is a conceptual model which was developed to simultaneously address importance of project management and risk management in software projects. This paper further refines this model by incorporating insights from experienced Thai software engineers, resulting in a more complete and practical project oriented risk management model which can be further applied in standard software projects. © 2011 IEEE.